2022
DOI: 10.3390/agronomy12020474
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Induced Physiological and Biochemical Regulations Confer Drought Tolerance in Pot Marigold (Calendula officinalis L.)

Abstract: Severe water stress conditions limit growth and development of floricultural crops which affects flower quality. Hence, development of effective approaches for drought tolerance is crucial to limit recurring water deficit challenges. Foliar application of various plant growth regulators has been evaluated to improve drought tolerance in different floricultural crops; however, reports regarding the role of chitosan (Ci) on seasonal flowers like calendula are still scant. Therefore, we evaluated the role of Ci f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…However, the highest SOD activity was observed in the plant treated with 90 ppm of CNPs subjected to 50% FC (2.38-fold of control). Several studies support our findings that chitosan and its nanoparticles have a favorable effect on antioxidant system gene expression and activation under DS [ 6 , 21 , 34 , 45 , 47 , 59 ]. In agreement with our study, Behboudi et al [ 15 ] observed the highest SOD activity level after foliar application of 90 ppm of CNPs to drought-stressed barley plants.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, the highest SOD activity was observed in the plant treated with 90 ppm of CNPs subjected to 50% FC (2.38-fold of control). Several studies support our findings that chitosan and its nanoparticles have a favorable effect on antioxidant system gene expression and activation under DS [ 6 , 21 , 34 , 45 , 47 , 59 ]. In agreement with our study, Behboudi et al [ 15 ] observed the highest SOD activity level after foliar application of 90 ppm of CNPs to drought-stressed barley plants.…”
Section: Discussionsupporting
confidence: 85%
“…Chitosan nanoparticles help improves water retention and RWC of stressed plants by reducing their transpiration rate, promoting water absorption and essential elements from roots, and regulating the cell osmotic pressure. Also, CNPs benefit from stomatal conductance and photosynthetic rate, then maintain water balance in cells by stomatal adjustment [ 6 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Foliar application of CTS also could effectively alleviate drought-induced growth inhibition of lettuce ( Lactuca sativa L.) plants [ 17 ]. In addition, the exogenous CTS significantly increased photosynthetic rate, water use efficiency, and CAT, POD, and SOD activities in pot marigold ( Calendula officinalis L.) plants, thereby mitigating deleterious effect of drought stress on growth [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, maize yields have been severely constrained in a number of developing countries due to a variety of abiotic and biotic stresses, as well as other causes ( Salika and Riffat, 2021 ). Drought, heat, and flooding are becoming more common, putting a burden on a number of vital crops, as a result of rising urbanization and habitat degradation as well as other unpredictable extreme climatic phenomena ( Javed et al, 2020 ; Ahmad et al, 2021 , 2022a ; Chowdhury et al, 2021 ; Salika and Riffat, 2021 ; Shabbir et al, 2021 ; Akhtar et al, 2022 ). Maize crop development is also challenged in the long run by the intensifying global climate.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, plants respond to drought stress in a variety of ways ( Gaufichon et al, 2010 ; Islam et al, 2021 ; Ahamd et al, 2022a ; Akhtar et al, 2022 ; Kumar et al, 2022 ; Shabbir et al, 2022 ). When plants are exposed to drought, they typically exhibit a series of morphophysiological changes associated with tolerance, including the maintenance of free proline accumulation, stomatal conductance, chlorophyll content, substomatal carbon dioxide concentration, canopy temperature, plant height, and stem diameter ( Mafakheri et al, 2010 ; Ali et al, 2011 ; Araus et al, 2012 ; Gao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%